Fractional thermoelasticity problem for a plane with a line crack under heat flux loading. Issue 10 (2nd December 2018) - Povstenko, Yuriy; Kyrylych, Tamara
Abstract: Symmetric stress distribution in an infinite isotropic plane with a line crack, in which surfaces are exposed to the heat flux loading is considered in the framework of fractional thermoelasticity. The heat conduction is described by the time-fractional heat conduction equations with the Caputo derivative of fractional order α . The solution is obtained using the integral transform technique and is expressed in terms of the Mittag-Leffler function. The stress intensity factor is calculated for different values of the order of fractional derivative. The numerical results are illustrated graphically.